Fixed Point Theory for Cyclic Generalized Weak 𝜙-Contraction on Partial Metric Spaces - Erdal Karapınar; I. Savas Yuce (Abstract and Applied Analysis)
A new fixed point theorem is obtained for the class of cyclic weak 𝜙-contractions on partially metric spaces. It is proved that a self-mapping 𝑇 on a complete partial metric space 𝑋 has a fixed point if it satisfies the cyclic weak 𝜙-contraction principle.